Penentuan Harga Opsi Put dan Call Terhadap Saham Nokia dengan Menggunakan Model Black-Scholes - Yogi Suprayogi; Nugraha Nugraha; Maya Sari; Nurul Hutami Ningsih (Universitas Kuningan, 2022)
Options are a derivative instrument. High volatility makes options an attractive investment. Volatility can describe risk or gain. Volatility describes the probability of a stock's price over a period of time. Nokia is the code used in the stock of Nokia Corporation. The research method used in this research is descriptive method. The price of the call option premium is determined by using the Monte Carlo simulation method. The data used is Nokia stock data, with the determination of the 3 month put option expiration period from October 2020 to October 2021. In this study, the recommended or non-recommended stocks were found in the buy and sell options with several option prices (last price) on both options. The researcher uses the black scholes model and it is found that Nokia shares are considered attractive to choose and become a recommendation for both buy and sell options for investors. Further findings can be seen in this study.